A corporate sustainability maturity model for readiness assessment: a three-step development strategy. Issue 5 (19th June 2020) - Sari, Yenny; Hidayatno, Akhmad; Suzianti, Amalia; Hartono, Markus; Susanto, Harman
Abstract : Purpose: One of the main challenges of organisations today is how to navigate their development into ideal sustainable organisations. However, each readiness level requires a different rubric of indicators. Therefore, this study develops a corporate sustainability maturity model (CSMM), which can be used by organisations to conduct self-assessments, identify their current sustainability maturity levels and transition into mature sustainable organisations. Design/methodology/approach: This CSMM comprises various maturity domains, sub-domains and levels as well as a rubric of indicators for assessing the maturity of corporate sustainability. In its development, a systematic literature review examined existing maturity models, after which a pilot study, based on the literature review, content analysis and expert interviews, was used to create a prototype of the CSSM. Finally, the model was refined and expanded by considering practitioners' feedback and the tendencies of other sustainability maturity models. Findings: On the basis of the findings, some Indonesian organisations conducted sustainability activities, without having a strategic plan. Moreover, the factors driving organisations to conduct sustainability efforts included external and internal pressure. However, typical factors, such as awareness of sustainability and organisational reputation gained from conducting sustainability activities, were insignificant in the sample. Originality/value: This CSMM is the first sustainability maturity model developed for readiness assessment in an Indonesian context. Through this CSMM, organisations can determine their current readiness level of sustainability maturity and choose the correct indicators to help improve each sustainability domain in the matrix.